Polstolet'ya nash gorod nosit lenina imya, slavit lenina imya, on delami svomi! - Nelyubin, F; Romanova, M
Image of Lenin, below a festive decorated alley [in Leningrad, St. Petersburg?] Original title: полстолетья наш город носит ленина имя, славит ленина имя, он делами своми! Suggested translation: For half a century our city bears Lenin’s name, praises Lenin’s name, he’s doing his own business! PO-2237